Synthesis of MgO nanocrystals with abundant surface defects via a carbonization method employing CO2 gas as starting material. (January 2017) - Hai, Chunxi; Zhou, Yuan; Du, Yongsheng; Sun, Yanxia; Zeng, Jinbo; Shen, Yue; Ren, Xiufeng; Li, Xiang; Zhang, Lijuan; Dong, Ouyang
Graphical abstract: Highlights: Synthesis of uniformly MgO nanoparticles via decomposition of Mg5 (CO3 )4 (OH)2 (H2 O)4 precursor prepared by bubbling CO2 gas. Proposing the formation mechanism of MgO nanoparticles. Investigating the relationship between crystal size and surface defects by comparing as-prepared and bought MgO nanoparticles. Abstract: Taking its unique property into consideration, uniformly dispersed MgO nanoparticles with abundant surface oxygen defects was primarily synthesized via a facile carbnization method employing CO2 gas as carburizer in this study. After reaction at 60 °C for 2 h, Mg 2+ ions were totally carbonized to caterpillar-like Mg5 (CO3 )4 (OH)2 (H2 O)4 precursor. And through decarbonization and dehydration processes during calcination, as-prepared Mg5 (CO3 )4 (OH)2 (H2 O)4 precursor with micro-nano structure was thouroughly converted to well-crystallized MgO nanospheres. As-evidenced by the UV–VIS-NIR diffuse reflectance spectroscopy, due to the largely intensified low-coordinated oxide ions at the corner and kink sites with decreasing the average size, the forbidden band gap of as-prepared MgO nanocrystals is 5.3 eV, which thus endows it intriguing applications in different fields.